2016
DOI: 10.18632/oncotarget.12533
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fibrinogen like protein 2 (sFGL2), the novel effector molecule for immunoregulation

Abstract: Soluble fibrinogen-like protein 2 (sFGL2) is the soluble form of fibrinogen-like protein 2 belonging to the fibrinogen-related protein superfamily. It is now well characterized that sFGL2 is mainly secreted by regulatory T cell (Treg) populations, and exerts potently immunosuppressive activities. By repressing not only the differentiation and proliferation of T cells but also the maturation of dendritic cells (DCs), sFGL2 acts largely as an immunosuppressant. Moreover, sFGL2 also induces apoptosis of B cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 108 publications
(140 reference statements)
2
18
0
Order By: Relevance
“…In clinical settings, serum and tissue sFGL2 levels are a surrogate for Treg activity in patients with chronic viral hepatitis C [23]. Our results indicated that sFGL2 may also be a surrogate for Treg activity in patients with CA [31].…”
Section: Discussionmentioning
confidence: 67%
“…In clinical settings, serum and tissue sFGL2 levels are a surrogate for Treg activity in patients with chronic viral hepatitis C [23]. Our results indicated that sFGL2 may also be a surrogate for Treg activity in patients with CA [31].…”
Section: Discussionmentioning
confidence: 67%
“…FGL2 is a member of the fibrinogen superfamily of proteins, which are mainly expressed by inflammatory cells, including macrophages, CD4 + T, CD8 + T, and endothelial cells [ 10 ]. FGL2 can oligomerize into a tetramer by forming interchain disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen-like protein 2 (FGL2) belongs to the fibrinogen-like protein family [ 10 ], which is mainly expressed in macrophages, T cells, endothelial cells, and tumor cells. FGL2 is a vital immune regulator of both innate and adaptive responses, with pleiotropic effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen-like protein 2 (FGL2) plays important roles in both innate and adaptive immunity (Liu, Liu & Chen, 2017). The FGL2 protein is located on the surface of endothelial cells and macrophages (Yang & Hooper, 2013).…”
Section: Introductionmentioning
confidence: 99%